2005
DOI: 10.1136/adc.2003.044255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for transmission of infection among children in household contact with adults having pulmonary tuberculosis

Abstract: Aims: To study the prevalence of tuberculosis infection among children in household contact with adults having pulmonary tuberculosis, and identify the possible risk factors. Methods: Children under the age of 5 years who were in household contact with 200 consecutive adults with pulmonary tuberculosis underwent tuberculin skin testing. Transverse induration of greater than 10 mm was defined as positive tuberculin test suggestive of tubercular infection. Infected children underwent chest radiography and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
4
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 12 publications
12
122
4
6
Order By: Relevance
“…The present study showed that, children of the wage laborer had the higher proportion of infection which corresponds to a study where children of service holders had significant reduced risk (p=0.039) to develop TB than others 10 . Increased size of household was found to be important in previous studies and overcrowding has been documented as a risk factor for TB from several other studies in a variety of settings [9][10]15 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study showed that, children of the wage laborer had the higher proportion of infection which corresponds to a study where children of service holders had significant reduced risk (p=0.039) to develop TB than others 10 . Increased size of household was found to be important in previous studies and overcrowding has been documented as a risk factor for TB from several other studies in a variety of settings [9][10]15 .…”
Section: Discussionsupporting
confidence: 88%
“…Child tuberculosis was found to be associated with educational attainment and also working status of mother in bivariate analyses but found not significant in multivariate analysis. Children of working mothers' had more chance to develop tuberculosis which contradicts previous studies 10 . Literate parents involved them in various jobs resulting less attention to their children.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This increase has been observed in adult smokers, as well as in non-smoking adults and children passively exposed to tobacco smoke. The risk for children passively exposed to tobacco smoke and tuberculosis was assessed in several studies in US [9], India [10], South Africa [11] and Spain [12]. The relative risk was proportional to the intensity and duration of exposure and is evaluated between 1.7 and 3.2.…”
Section: Risk Of Infection (If Exposed)mentioning
confidence: 99%
“…Temaslının immunsupresif, beş yaşından küçük veya 60 yaşından büyük olması hastalık riskini oldukça arttırmaktadır [11]. Ancak 15 yaş altı temaslı-lar önemli bir risk grubunu oluşturmaktadır.…”
Section: Olgularunclassified